STRESS MANAGEMENT SURVEY OF NURSING STUDENTS IN FACE TO FACE LEARNING POST ONLINE LEARNING: A CROSS-SECTIONAL STUDY - Dwiharini Puspitaningsih; Yudha Laga Hadi Kusuma (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2023)
Background: Almost two years of online learning, finally in early 2022 the Indonesian government began to implement a face-to-face learning model. This can trigger stress for students who will return to carrying out offline learning. Purpose: This study aims to determine stress management in terms of gender, education level, and place of residence for undergraduate nursing students in the Mojokerto district. Methods: Correlation analytic research design with a cross sectional approach of 85 nursing students. The instrument used in the study was a modified questionnaire by researchers who had been tested on the instrument. Results: Showed that almost half of the respondents carried out stress management by listening to music by 18 students (21,2%), surfing the internet by 16 students (18,8%) and praying/listening to prayers by 14 students (16,5%). Conclusion: Stress management that is done to deal with stress on each student has relatively the same characteristics. This is possible because students live in the same area and the characteristics of students in relatively the same year are almost the same. Universities, especially the College of Health Sciences, can provide more facilities for students in reducing stress in order to improve the results and quality of education. Abstrak Latar Belakang: Setalah dua tahun pembelajaran daring dilaksanakan, pada awal tahun 2022 pemerintah Indonesia mulai memberlakukan model pembelajaran tatap muka. Hal tersebut dapat memicu stress bagi mahasiswa yang akan kembali melaksanakan pembelajaran luring. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui manajemen stres ditinjau dari jenis kelamin, tingkat pendidikan, dan tempat tinggal pada mahasiswa S1 Keperawatan di wilayah Kabupaten Mojokerto. Metode: Desain penelitian analitik korelasi dengan pendekatan cross sectional pada 85 mahasiswa keperawatan. Instrumen yang digunakan dalam penelitian adalah kuisioner modifikasi peneliti yang telah dilakukan uji coba instrumen. Hasil: Menunjukkan hampir setengah responden melakukan manajemen stres dengan mendengarkan musik sebanyak 18 mahasiswa (21,2%), berselancar internet sebanyak 16 mahasiswa (18,8%) dan berdoa/ mendengarkan doa sebanyak 14 mahasiswa (16,5%). Kesimpulan: Manajemen stress yang di lakukan untuk mengatasi stress pada masing-masing mahasiswa memiliki karakteristik relatif sama. Hal tersebut dimungkinkan karena mahasiswa berdomisili di wilayah yang sama serta karakteristik mahasiswa pada tahun yang relatif sama juga hampir sama. Perguruan tinggi khususnya Sekolah Tinggi Ilmu Kesehatan dapat lebih memberikan fasilitas mahasiswa dalam menurunkan stres agar dapat meningkatkan hasil dan kualitas pendidikan.